INITIATING VOCATIONAL EDUCATION IN PESANTREN: EFFORTS TO IMPROVE STUDENT COMPETENCIES TO FACE THE CHALLENGES OF GLOBALIZATION - Fajarudin, Akhmad Afnan; Zahroh, Aminatuz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses how pesantren can develop the vocational skills of students through curriculum adaptation based on community needs, technology, and the job market. With the legal foundation of Law Number 18 of 2019 concerning Islamic Boarding Schools, these institutions can independently develop curricula that emphasize life skills, including technology, agribusiness, and entrepreneurship, without losing their Islamic identity. This research uses a qualitative method based on literature review, with relevant literature analysis. The research results show that pesantren are capable of creating outstanding students through the integration of religious and vocational education, thereby empowering the community, reducing unemployment, and improving the quality of life for the students. This research emphasizes the importance of collaboration between pesantren, vocational schools, and universities to strengthen the role of pesantren as centers of Islamic life skills-based education. Keywords: Pesantren, Vocational Education, Santri Competence